Pedoman Perancangan Fasilitas Parkir Di Pantai Mengening: Bahasa Indonesia - I Made Pasek Guna Pratama; Made Anggita Wahyudi Linggasani; Agus Kurniawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Mengening Beach is one of the beaches in Cemagi Village which is a tourist attraction as well as an icon of the Cemagi Tourism Village which is crowded with visitors. Adequate parking facilities are one of the important things to support tourist comfort when visiting Mening Beach. Guidelines for designing good parking facilities are needed in order to create comfortable, safe and efficient parking facilities which cover several aspects such as location selection, capacity, layout, access, and the use of appropriate technology. The choice of location takes into account accessibility, environmental conditions, and safety. A good layout will make it easier for car and motorcycle drivers to get out of the parking lot or to park their vehicles. Designing good parking facilities at Mening Beach can help improve the quality of the tourist experience, as well as increase the safety and comfort of the parking area. This design guideline can be a reference for the government and managers of coastal tourism objects in building effective and efficient parking facilities to support the success of tourism objects..